Immune Cell Proteins and Parkinson's Disease: A Mendelian Randomization Analysis of Causal Associations - Haining Li; Jianhang He; Tingting Xuan; Shue Gu; Xiaoyan Niu; Yazhou Ren; Xiuping Zhan; Jiang Cheng (Brain and Behavior)
Abstract Background The neuroimmune interaction mechanisms of neurodegenerative diseases have received increasing attention. Parkinson's disease (PD) is the second most common neurodegenerative disease, with potential immunoregulatory abnormalities. However, the causal roles of specific immune cell proteins remain unclear. Methods We obtained PD and immune cell protein data from an open and free genome‐wide association study (GWAS) for subsequent analysis. Two‐sample MR analyses with inverse‐variance weighted (IVW), MR‐Egger regression, weighted median, and weighted mode methods were used to evaluate the causal effects. Sensitivity analyses incorporated Cochran's Q test for SNP heterogeneity (prioritizing IVW estimates when present) alongside MR‐Egger intercept and leave‐one‐out evaluations to address horizontal pleiotropy. Results The IVW analysis revealed that the genetically predicted level of three immune cell proteins per standard‐deviation increase was positively associated with PD, including CD38 (OR = 1.13, 95%CI: 1.05–1.22, P = 0.001), FcγRIIIB (OR = 1.06, 95%CI: 1.01–1.11, P = 0.019), and CUL4B (OR = 1.11, 95% CI: 1.00–1.20, P = 0.012). The IVW analysis also revealed that the genetically predicted level of ADAMTSs per standard‐deviation increase was inversely associated with PD (OR = 0.89, 95% CI: 0.81–0.98, P = 0.013). Conclusions We demonstrate that CD38, FcγRIIIB, and CUL4B are risk factors for PD, whereas ADAMTSs is a protective factor.